CREATIVITY SUPPORT TOOLS: Accelerating Discovery and Innovation. - Shneiderman, Ben (Communications of the ACM, 2007)
The article discusses the role of software in enhancing individual creativity. Early software development focused on increasing economic productivity. A more recent and greater challenge is to produce "creativity support tools." Guiding principles for tool designers include an openness to exploration and collaboration, and a willingness to produce tools that are easy for novices to use, yet suitably ambitious for experts. Traditional benchmarking is not apt be appropriate in such relatively unstructured environments.